2015
DOI: 10.1080/02640414.2015.1099715
|View full text |Cite
|
Sign up to set email alerts
|

A new injury prevention programme for children’s football – FIFA 11+ Kids – can improve motor performance: a cluster-randomised controlled trial

Abstract: The present study evaluated the effects of a newly developed injury prevention programme for children's football ("FIFA 11+ Kids") on motor performance in 7-12-year-old children. We stratified 12 football teams (under-9/-11/-13 age categories) into intervention (INT, N = 56 players) and control groups (CON, N = 67). INT conducted the 15-min warm-up programme "FIFA 11+ Kids" twice a week for 10 weeks. CON followed a standard warm-up (sham treatment). Pre- and post-tests were conducted using: single leg stance; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
154
3
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(175 citation statements)
references
References 30 publications
8
154
3
10
Order By: Relevance
“…Similar risk factors have been associated with acute knee injuries as well 31 32. Enhancing knee alignment and lower extremity/core strength might be of value in children participating in football in order to reduce the risk of both acute and overuse knee injuries21 as well as to improve motor performance 33…”
Section: Discussionmentioning
confidence: 99%
“…Similar risk factors have been associated with acute knee injuries as well 31 32. Enhancing knee alignment and lower extremity/core strength might be of value in children participating in football in order to reduce the risk of both acute and overuse knee injuries21 as well as to improve motor performance 33…”
Section: Discussionmentioning
confidence: 99%
“…Each exercise includes five difficulty levels. The program starts from level one and progresses to level five gradually (18).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, two distinct parts of the 11+ Kids program are allocated to plyometric and jumping exercises. Rossler et al (2015) investigated the effects of this program on the kids' neuromuscular performance compared to a regular warm-up program and showed the effectiveness of this program in enhancing the kids' motor performance (18). FIFA intends to expand and develop the FIFA 11+ Kids comprehensive warmup program.…”
Section: Introductionmentioning
confidence: 99%
“…Balance has been considered one of the most important fundamentals for non‐contact injuries prevention and rehabilitative training effects assessment in sport. Despite the relationship between balance and sport injury risk has been established, the relationship between balance and sport performance still remains unclear …”
Section: Introductionmentioning
confidence: 99%
“…Rossler et al found slight performance enhancements in dynamic balance, agility, jumping performance, and slalom dribbling in young soccer players (7‐12 years) after a specific injury prevention program (FIFA 11 + Kids). This program, which includes six exercises for lower limbs and trunk stability and strength, and one exercise on falling technique, was also more effective in injury prevention than a usual warm‐up .…”
Section: Introductionmentioning
confidence: 99%